Determinants of Customer Satisfaction in Lighting and Electrical MaintenanceCompany PLP Based on the IPA and Kano Model - Rohmah, Aniq Jazilatur Rohmah; Singgih, Moses Laksono Singgih (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
Service quality is a fundamental principle of a service-oriented firm. High service quality is crucial forservice organizations to remain competitive and retain customers, preventing them from switchingto other providers. PLP is a firm that specializes in providing maintenance services for electrical andlighting systems. With a sample size of 28 respondents, a preliminary customer satisfaction surveywas conducted. The survey revealed that 32% of the customers were dissatisfied with the service,while 7% were very dissatisfied. However, these scores did not meet the desired level of maximumcustomer satisfaction. The objective of this study is to evaluate the level of customer satisfaction withthe electrical and lighting maintenance services provided by PLP, and to identify the specific featuresthat need improvement and should be given priority. This research employs the amalgamation ofservice quality, importance-performance analysis (IPA), and Kano techniques. The disparity betweenthe significance and execution is seen in customer satisfaction. A survey was sent to a total of 45patrons of PLP Company. SPSS determined all the questions in this questionnaire on five qualityfactors. The study's gap scores for dependability, responsiveness, assurance, empathy, and tangiblesare as follows: -0.364, -0.409, -0.467, -0.462, and -0.111. This suggests that consumers of PLP aredissatisfied. Subsequently, this research identified six service qualities that need improvement.